Proceedings of the 2nd LACCEI International Multiconference on Entrepreneurship, Innovation and Regional Development (LEIRD 202 2022
DOI: 10.18687/leird2022.1.1.95
|View full text |Cite
|
Sign up to set email alerts
|

Electricity generation and wastewater treatment using microbial fuel cells with graphite and aluminum electrodes

Abstract: A microbial fuel cell (MFC) is a system that can integrate electricity generation and, at the same time, contribute to decontaminating wastewater, becoming an eco-friendly technology with the environment. In this research, microbial fuel cells with graphite and aluminum electrodes were used at different sizes: 9, 25 and 64 cm 2 , and a wastewater sample obtained from a rural location in Peru was used as substrate. The MFCs parameters of voltage, current and conductivity were monitored for 12 days, for the gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
1
1
Order By: Relevance
“…The voltage values obtained are higher than those reported by Bose et al (2023) where they used wastewater from the sugarcane industry in MFC with biomass-derived activated carbon as the cathode and pretreated carbon wire-based brush as the anode and managed to produce maximum voltage peaks of 870 ± 20 mV [44], and Agüero-Quiñones et al (2022), who used municipal wastewater in MFC-SC with aluminum as the cathode and graphite as the anode, generating maximum values of 220 mV. Compared to our research, it may be due to the fact that the aluminum electrodes used do not have as good conductive properties as the zinc or copper used as connectors [45]. Figure 3b shows the values of electric current the cells produce during monitoring.…”
Section: Measurement Of Electrochemical Parameters Of Mfcscontrasting
confidence: 40%
“…The voltage values obtained are higher than those reported by Bose et al (2023) where they used wastewater from the sugarcane industry in MFC with biomass-derived activated carbon as the cathode and pretreated carbon wire-based brush as the anode and managed to produce maximum voltage peaks of 870 ± 20 mV [44], and Agüero-Quiñones et al (2022), who used municipal wastewater in MFC-SC with aluminum as the cathode and graphite as the anode, generating maximum values of 220 mV. Compared to our research, it may be due to the fact that the aluminum electrodes used do not have as good conductive properties as the zinc or copper used as connectors [45]. Figure 3b shows the values of electric current the cells produce during monitoring.…”
Section: Measurement Of Electrochemical Parameters Of Mfcscontrasting
confidence: 40%
“…Other investigations also showed a decrease in current in the last few days; for example, Commault et al (2017) reported a reduction in current due to a decrease in microbial activity or a decrease in the efficiency of electron transfer in the biofilm [51]. Likewise, Rojas-Flores et al ( 2023) mention that as the organic matter in the medium decreases, there will be a decrease in electrons, which brings a decrease in the generation of electric current [52].…”
Section: Production Of Electrical Energy In Mfc During the Experiment...mentioning
confidence: 98%